Construction of organoids using bioprinting technology: a frontier exploration of cartilage repair - Jingtao Huang; Shicheng Jia; Rongji Liang; Aikang Li; Lin Li; Haojian Wang; Jiayou Chen; Haoxian Tang; Xuan Zhang; Jianjing Lin; Xintao Zhang (Journal of Orthopaedic Translation)
Articular cartilage defects caused by trauma or degeneration severely impair patient function. Cartilage repair organoids represent a transformative approach in regenerative medicine to address these challenges. This review focuses on the development and therapeutic potential of such organoids, detailing their role in overcoming limitations of conventional treatments. Central to this progress, bioprinting technology enables precise organoid fabrication by advancing organoid-compatible bioinks and printing techniques. We further examine applications in disease modeling and drug screening, alongside pathways for clinical translation. As organoid engineering matures, it promises to deliver effective, patient-specific solutions for cartilage restoration.The Translational Potential Statement: The Translational Potential of this Article: 3D-bioprinted cartilage organoids exhibit outstanding efficacy in animal models and hold promise for future clinical trials. The bioinks and printing technologies are distilled to promote basic research toward translation of cartilage repair.